Intensive passive static stretching and inflammation - Apostolopoulos, N. (New Studies in Athletics, 2017)
Sports coaches and medical professionals have traditionally advocated stretching exercises as a means for performance enhancement and injury prevention. Previous research shows that, when compared to ballistic stretching, static stretching is associated with a greater release of creatine kinase, an indicator of stress and tissue damage, and higher levels of delayed onset muscle soreness. The aim of this study was to investigate whether acute intensive passive static stretching causes an inflammatory response. A randomised within-subject crossover trial examined the effects of intensive passive static stretching on selected serum-based muscle inflammation biomarkers. Twelve healthy, recre-ationally active males participated in both intensive passive static stretching and control interventions. The hamstrings, gluteals, and quadriceps were stretched at a level rated as "discomfort and/or mild pain" on a numerical scale. During the control intervention, the participants rested for a time equivalent to the intensive passive static stretching intervention. Blood samples collected pre-, immediately post-, and at 24 hours post-intervention showed that high sensitivity C-reactive protein [hsCRP] increased significantly for intensive passive static stretching immediately and 24 hours after, for time (p=0.05) and time x condition (p=0.006) compared to control. This indicates that intensive passive static stretching may lead to an.acute inflammatory response.